A flow of funds analysis of the US quantitative easing. Issue 2 (3rd April 2018) - Tsujimura, Kazusuke; Tsujimura, Masako
ABSTRACT: After the Bank of Japan first introduced a quantitative easing policy in 2001, Tsujimura and Mizoshita [(2003) Asset-Liability-Matrix Analysis Derived From Flow-of-Funds Accounts: the Bank of Japan's Quantitative Monetary Policy Examined. Economic Systems Research, 15, 51–67] applied input–output analysis to analyze its effects. Some central bankers criticized the analysis as misleading because it was based on the asset–liability matrix derived from the financial balance sheets. In this vein, the real policy effects on production and employment were overlooked. Herein, we answer such criticism by introducing a new method of tracking the flow of funds. It covers both real and financial transactions to show the mechanism and the effects of the US quantitative easing.